2018
DOI: 10.1155/2018/6823638
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Serological Survey of Human Fascioliasis in Canutama Municipality in Western Amazon, Brazil

Abstract: Background Fascioliasis is an important parasitic disease. In the northern region of Brazil, a human parasite infection has been reported through a coprological survey. Eggs of Fasciola hepatica were found in fecal samples of 11 individuals. Knowledge of the infection in animals or the presence of snails is necessary to address the possibility of the parasite cycle occurrence in that region. The aim of this study was to describe the transmission of human fascioliasis in Canutama, Amazonas, in Western Amazonia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…infections were detected. Oliveira et al (2007) observed the prevalence of 2% Fasciola hepatica, as did we in a previous study (Maciel et al, 2018) that involved a serological survey of human fascioliasis in the same patients that constitute the population of this study, which shows the prevalence (1.8%) of F. hepatica eggs in their feces. This, however, was evidenced in a single patient and after a second collection of feces.…”
Section: Discussionsupporting
confidence: 85%
“…infections were detected. Oliveira et al (2007) observed the prevalence of 2% Fasciola hepatica, as did we in a previous study (Maciel et al, 2018) that involved a serological survey of human fascioliasis in the same patients that constitute the population of this study, which shows the prevalence (1.8%) of F. hepatica eggs in their feces. This, however, was evidenced in a single patient and after a second collection of feces.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with similar previous studies, a detailed clinical history was recorded for all participants regarding sociodemographic characteristics and potential sources of infection based on the characteristics of the participants and the study locality [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary definitive hosts of Fasciola parasites are the domestic ruminants (Khanjari et al 2014), while humans become accidentally infected (Nguyen et al 2018). Fasciolosis has been identified as a neglected tropical disease where over 180 million people in 75 countries are at risk of being infected (Liu et al 2014;Maciel et al 2018). Globally, over 600 million animals are at risk of getting infected with Fasciola parasites (Maciel et al 2018;Rehman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fasciolosis has been identified as a neglected tropical disease where over 180 million people in 75 countries are at risk of being infected (Liu et al 2014;Maciel et al 2018). Globally, over 600 million animals are at risk of getting infected with Fasciola parasites (Maciel et al 2018;Rehman et al 2016). Fasciolosis causes massive economic burden in the livestock enterprise as a result of decreased animal productivity, characterised by reduced growth rate, low quality meat and milk, infertility and diseases (Rehman et al 2016;Shahzad et al 2012).…”
Section: Introductionmentioning
confidence: 99%